The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.4149/km_2014_6_361
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of as-cast and extruded Mg-4Zn and Mg-4Zn-0.4Ca alloys

Abstract: This work studied the effect of extrusion and alloying with 4 wt.% of Zn and 0.4 wt.% of Ca on the structure and mechanical properties of magnesium. Light, scanning electron microscopy, X-ray diffraction, hardness, compressive and tensile tests were used for this purpose. The addition of zinc led to the formation of MgZn and further alloying with calcium changed the nature of the secondary phase to Ca2Mg6Zn3. The process of extrusion resulted in significant structural refinement, which was the most pronounced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Hradilova and Vojtech *Corresponding author: tel. : +91 9471192246; fax: +92 326 229 6563; e-mail address: mal123 us@yahoo.com [7] have demonstrated that the extrusion process and the addition of small wt.% of Zn and Ca in Mg make significant structural refinement leading to substantial improvement in tensile strength. Further, Li et al [8] have exposed that continuous variable cross-section direct extrusion (CVCDE) process gives more grain refinement over the conventional extrusion process, and correspondingly the tensile strength can be enhanced more as compared to the ordinary extrusion process.…”
Section: Introductionmentioning
confidence: 99%
“…Hradilova and Vojtech *Corresponding author: tel. : +91 9471192246; fax: +92 326 229 6563; e-mail address: mal123 us@yahoo.com [7] have demonstrated that the extrusion process and the addition of small wt.% of Zn and Ca in Mg make significant structural refinement leading to substantial improvement in tensile strength. Further, Li et al [8] have exposed that continuous variable cross-section direct extrusion (CVCDE) process gives more grain refinement over the conventional extrusion process, and correspondingly the tensile strength can be enhanced more as compared to the ordinary extrusion process.…”
Section: Introductionmentioning
confidence: 99%